Sur l’estimation d’un système complet de demande sous rationnements quantitatifs - Bronsard, Camille; Salvas-Bronsard, Lise (L'Actualité économique, 1979)
The paper is divided into two parts. In the first one, three complete systems of demand equations are derived, namely, the standard neo-classical model, a model under quantity rationing and the general reduced form of walrasian models. The standard neo-classical model has no spillover eflects while the other models allow for them. But the spillover effects of the general reduced form are walrasian while the spillover effects of the model with quantity rationing can be specified as keynesian.In the second part of the paper, the authors try to discriminate among these forms on empirical grounds. As a matter of fact, each model is found consistent with the Canadian data and the authors conclude that to discriminate between the models, one must insert them into more general models.